Evaluation of antimicrobial activity of chlorhexidine-containing oral gels against aspiration pneumonia-inducing bacteria: An In Vitro study - Sun-Young Han; Jiyeon Roh; Yun-Sook Jung; Ki-Rim Kim (Wolters Kluwer Medknow Publications, 2022)
Aim: Hospitalised patients have a high risk of developing aspiration pneumonia because of poor oral care and oral microbial flora changes. Chlorhexidine (CHX) solution has been used to reduce inflammation and prevent infections in oral cavity, but it is difficult to use in inpatients. Gel-type antimicrobial agents rather than the liquid form may be effective for the oral management of hospitalised patients. Therefore, we evaluated the in vitro antimicrobial effects of CHX-containing oral gels on aspiration pneumonia-inducing bacteria compared to the CHX solution. Materials and Methods: The experimental products of two oral gel types containing 1% and 0.1% CHX, respectively, were selected. Hexamedine, a 0.12% CHX solution, was used as a positive control. The antimicrobial activity of CHX agents against six pneumonia-causing bacteria and Streptococcus mutans, one of the most common oral bacteria, was comparatively analysed using the agar disk diffusion method. Results: In the disk diffusion assay, the 1% CHX gels showed the highest inhibitory effect on all bacteria. All CHX agents including gels and solution had the highest antibacterial activity against Staphylococcus aureus compared with other bacteria. Conclusions: We confirmed the significant antimicrobial effects of the 1% CHX oral gels on aspiration pneumonia-inducing bacteria. These results suggest that CHX gels may be an effective oral care method for preventing infection in inpatients who have difficulty using the solution.